Optimal Decisions for Adoption of Item-Level RFID in a Retail Supply Chain with Inventory Shrinkage under CVaR Criterion - Chunming Xu; Daozhi Zhao (Discrete Dynamics in Nature and Society)
This paper investigates the effect of item-level RFID on inventory shrinkage in the retail supply chain, which consists of a risk-neutral manufacturer and a risk-averse retailer. Under conditional value-at-risk (CVaR) criterion, two different supply chain settings are discussed as follows. In the centralized setting, we develop the models in both RFID case and no RFID case, respectively. Comparisons between the two cases are made. In particular, a sufficient condition is given to judge whether to adopt item-level RFID. In the decentralized setting, we focus on discussing two different contract types including wholesale price contact and revenue sharing contract. Finally, number examples and sensitivity analysis are given to illustrate the proposed models. The results show that, for the centralized system, the sales-available rate, the recovery rate, and the tag cost are mainly the driving factors in evaluating the benefit of an item-level RFID. In particular, when the sales-available rate and the tag cost are quite small and the recovery rate is higher, the supply chain partners’ profits obtained by investment for RFID are improved significantly. For the decentralized system, under revenue sharing contract, Pareto improving outcome and coaffording risk can be achieved if the retailer sets an appropriate parameter for the manufacturer.